2019
DOI: 10.31665/jfb.2019.7198
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability and transport of apigenin across Caco-2 cell monolayers

Abstract: Investigation on bioavailability was carried out by determining the absorption and transport of bioaccessible apigenin from Mangifera indica (Water Lily var.) into Caco-2 human intestinal cell using a reliable and sensitive analytical method of LC-MS/MS. Results revealed that the concentration of glucuronidated apigenin lower than apigenin. The apigenin was metabolised inside the cells through glucuronidation process, and cross the monolayer to reach the basolateral sides or effluxed back to the apical side. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These results suggest possible differences in matrix-dependent transport efficacy, similar to findings from the study by Hilary et al (2020), which showed differences in transport efficacy between different forms of date seeds. The disparities in transport efficiency between phenolic compounds can be attributed to the chemical structure and solubility of the compounds as well as differences in the transport mechanism (Fang et al, 2017;Marina et al, 2019). The transportation of simple phenolic acids, such as protocatechuic acid and vanillic acid, and flavonoid aglycones, such as chrysoeriol, is likely facilitated by direct passive diffusion.…”
Section: B Tracementioning
confidence: 99%
“…These results suggest possible differences in matrix-dependent transport efficacy, similar to findings from the study by Hilary et al (2020), which showed differences in transport efficacy between different forms of date seeds. The disparities in transport efficiency between phenolic compounds can be attributed to the chemical structure and solubility of the compounds as well as differences in the transport mechanism (Fang et al, 2017;Marina et al, 2019). The transportation of simple phenolic acids, such as protocatechuic acid and vanillic acid, and flavonoid aglycones, such as chrysoeriol, is likely facilitated by direct passive diffusion.…”
Section: B Tracementioning
confidence: 99%
“…Many efforts have been made in unrevealing the digestion and absorption of phenolic compounds [ 21 , 22 ], all of which help in better understanding their systemic effects as non-metabolized and/or non-absorbed phenolics in exerting their effects locally upon gastric digestion [ 2 ]. Furthermore, lipase and alpha-glucosidase are involved in the digestion of triacylglycerols and carbohydrates, respectively [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%